Ontario University System Financing and Staffing Policies A Quantitative Model for Policy Analysis - Smith, Richard (Canadian Journal of Higher Education, 1976)
This paper presents a computer based model of the Ontario university system. The em- phasis is on funding, faculty staffing and faculty salaries from 1955 to 1995. Recent events in these areas are analyzed and explained as consequences of interaction between a strong- ly self-equilibrating social system, the universities, and a massively disequilibrating external force, the expansionary drive of the 1960's. Many past and present characteristics of the university system are seen as temporary abberations, a return to which is not possible. The effects of several proposed modifications to funding, staffing and salaries policies are ex- plored, as are prerequisites for a return to "steady state ". While a technical appendix is available which specifies and discusses the equations employed in the computer model, this paper is intended for a non-technical readership whose primary interest is the subject matter dealt with.